Evaluación de la implementación de mallas piramidales plus en shakers derrick en la perforación de dos pozos en la cuenca del Putumayo con fluido base aceite (2020)
In the present dissertation a technical and financial evaluation of the implementation of pyramidal plus meshes in Derrick shakers for the drilling of two wells in the Putumayo Basin is made, for it a study of the behavior and the properties of the system of primary control of solids and the meshes implemented in the perforation of these wells was made. In order to carry out a representative analysis, the results obtained during the drilling of two wells adjacent to the study zone using conventional meshes were considering, so that the conditions in both wells were similar. To obtain the results and the necessary information, mud density, retort and fluid screening tests were carried out to evaluate the performance of both conventional and pyramid plus meshes.